ANALISIS SWOT UNTUK STRATEGI PENGEMBANGAN UKM SUPPLAY PASIR DAN BATU - Riska Amelia; Nekky Rahmiyati; Yulyar Kartika Wijayanti (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
This research discusses the development strategy of the sand and stone supply business at CV Putri Raja in Gempol, Pasuruan using SWOT analysis. CV Putri Raja has great market potential to compete with competitors. The purpose of this research is to identify internal and external factors affecting the business, formulate a development strategy, and determine the most appropriate strategy. The methods used include Business Model Canvas (BMC) to map the business model, SWOT analysis, IFAS and EFAS matrix, and economic analysis to determine the Break Even Point (BEP). The results showed that CV Putri Raja has dominant strengths compared to weaknesses, the company is in quadrant I which means it has a strong competitive position. The development strategy that can be used is to focus on taking advantage of internal strengths and external opportunities (S-O strategy). The development strategy is to improve service quality and maintain stable stock availability, take advantage of massive development opportunities in East Java and open market network access to contractors as business partners, improve management management and improve the quality of human resources through training, take advantage of social media for branding and massive promotion, maintain price stability and quality of sirtu and delivery services, consistently apply industrial K3 in every production process, add dumtruck technicians & periodic driver tests to minimise fleet constraints in delivery services. Keywords: Development Strategy, SWOT Analysis, Business Model Canvas, UKM